Can Subaltern Exist? Reinterpreting the Issue of Subalternity (Case Study of Blimbingsari Village - Jembrana Regency and Pegayaman Village - Buleleng Regency) - Hamel, Victorius; Suryawan, Dewa Ketut; Sumawidayani, Nyoman (P4W IPB, 2024)
The objective of this study is to further elucidate a significant inquiry posed by Gayatri Spivak, namely, the ability of the subaltern to articulate their voice. This inquiry's significance arises within the context of social interactions, where there are discernible patterns of social dominance. Is it possible for a social group to survive without the active participation and expression of its members? This study aims to investigate how a village can persist within a social, cultural, and political framework that actively conceals its presence. The aforementioned pressure is commonly acknowledged as an inherently social phenomenon, indicating the presence of a mechanism of social hegemony. The hegemonic process is enacted through the implementation of village norms, particularly about customary villages (desa adat). The majority of villages in Bali adhere to a dual system of governance, consisting of office villages (desa dinas) and customary villages desa adat. Nevertheless, it is worth noting that the focus of this research lies solely on two specific villages, both of which adhere to a single type of governance known as the official village. The two villages under consideration are Blimbingsari in the Jembrana district and Pegayaman in Bali's Buleleng district. Both communities remain independent settlements in Bali to this day. Nevertheless, the dynamics and obstacles that exist are not straightforward. This research tries to listen to the voices of the subaltern and classifies them into four main issues, namely: 1) cultural politics; 2) political economy; 3) Ideology; 4) Conscientization. Through these four issues, an understanding of how these two villages continue to exist amid existing social harmonization is obtained.